The Application of Electroencephalogram in Driving Safety: Current Status and Future Prospects - Peng, Yong; Xu, Qian; Lin, Shuxiang; Wang, Xinghua; Xiang, Guoliang; Huang, Shufang; Zhang, Honghao; Fan, Chaojie (Frontiers in Psychology, 2022)
The driver is one of the most important factors in the safety of the transportation system. The driver’s perceptual characteristics are closely related to driving behavior, while Electroencephalogram (EEG) as the gold standard for evaluating human perception is non-deceptive. It is essential to study driving characteristics by analyzing the driver's brain activity pattern, effectively acquiring driver perceptual characteristics, creating a direct connection between the driver's brain and external devices, and realizing information interchange. This paper first introduces the theories related to EEG, then reviews the applications of EEG in scenarios such as fatigue driving, distracted driving, and emotional driving. The limitations of existing research have been identified and the prospect of EEG application in future brain-computer interface automotive assisted driving systems have been proposed. This review provides guidance for researchers to use EEG to improve driving safety. It also offers valuable suggestions for future research.